An Integrated Mindfulness Intervention For Emotional Numbness In Major Depression: A Case Study - Rahmawati, Adelina (Seurune : Jurnal Psikologi Unsyiah, 2025)
This single-case study aims to examine the effectiveness of an integrated mindfulness-based intervention in reducing symptoms of emotional numbness in major depressive disorder. A 30 year old female participant with severe depression (BDI-II = 29) received 12 individual sessions combining mindfulness-based cognitive therapy, body-centered mindfulness, and compassion-focused therapy at a private psychology clinic. Data were collected through clinical interviews, systematic observation, and the BDI-II instrument. The result showed a significant reduction in depressive symptoms, with the BDI-II score decreasing to 14 (mild depression) after the intervention and further decreasing to 12 at the one-month follow up session. Thematic analysis revealed enhanced emotional awareness, improved emotional expression, and reduced self-criticism. These findings suggest that a structured mindfulness approach can effectively address emotional numbness in depression, offering promising implications for clinical practice. However, single case findings require replication before generalization.Abstrak: Penelitian studi kasus tunggal ini bertujuan untuk mengkaji efektivitas intervensi berbasis mindfulness dalam mengurangi simptom emotional numbness pada individu dengan gangguan depresi mayor. Partisipan adalah seorang Perempuan berusia 30 tahun dengan tingkat depresi berat (skor BDI-II = 29). Data dikumpulkan melalui wawancara klinis, observasi sistematis, dan instrumen BDI-II. Intervensi terdiri dari 12 sesi individual yang mengintegrasikan mindfulness-based cognitive therapy, body-centered mindfulness, dan compassion-focused therapy. Hasil penelitian ini menunjukkan penurunan signifikan pada gejala depresi dengan skor BDI-II menjadi 14 (depresi ringan) setelah intervensi dan skor 12 pada sesi follow up setelah satu bulan sesi selesai. Selain itu, partisipan menunjukkan peningkatan kesadaran emosional, ekspresi emosi yang lebih baik, dan penurunan sikap kritik diri. Temuan ini menunjukkan bahwa pendekatan mindfulness yang terstruktur efektif dalam mengatasi emotional numbness dan mendukung pemulihan psikologis pada gangguan depresi mayor.